Integrated Organic Farming System: an innovative approach for enhancing productivity and income of farmers in north eastern hill region of India - DAS, ANUP; LAYEK, JAYANTA; I, RAMKRUSHNA G; BABU, SUBHASH; DEVI, M THOITHOI; DEY, UTPAL; SUTING, D; YADAV, GULAB SINGH; LYNGDOH, DAPHI BANRI D; PRAKASH, NARENDRA (The Indian Journal of Agricultural Sciences, 2019)
About 85% farmers of the north eastern hill region (NEHR) of India are small and marginal. Hence, there is need for establishing package of practices in an integrated manner to enhance on-farm resource recycling, employment, income and sustain soil health. An integrated organic farming system (IOFS) model (0. 43 ha) was assessed during 2005- 2017 at ICAR Research Complex for NEH Region, Umiam, Meghalaya (960 m ASL) with diversified farming components like field crops, horticultural crops, livestock (one cow + calf) along with perennial fodder crops, central water harvesting pond for composite fish culture and as a source for irrigation during lean season and provision for nutrient recycling. The productivity and income from the on farm IOFS model was compared with the ruling farmers practice-I (Monocropping, i.e. rice-fallow system) and farmers practice-II (cultivating about 30% farm area for second crop like vegetables after rice). The average results indicated that the rice equivalent yield (REY) from the IOFS model was 19. 8 t/ha as against 4 t/ha and 6.72 t/ha from the farmers practice-I and II, respectively. The enhancement in net income due to IOFS was 355 and 191% relative to farmers practice -I and II, respectively. The IOFS model could meet 92, 82 and 96% (N, P2O5 and K2O) of its nutrient demand within the system. The IOFS model was also replicated in farmers’ field through participatory approach in three villages covering about 110 ha area and 317 households during 2013 to 2017. After 4 years, on an average farmers productivity of various crops (tomato, potato, chili, carrot, French bean, ginger and turmeric) enhanced by 15 to 45% and annual income enhanced by about ` 15500 per house hold. Thus, IOFS could be a viable option for organic food production and sustainable agricultural development in the hill ecosystem of north east India.